Population density of the peanut worm Siphonosoma australe australe (Keferstein, 1865) (Sipunculus: Phascolosomatidae) in the mangrove forest of Gianh river, Quang Binh province - My Huong, Nguyen Thi; Chung, Ngo Dac; Ba, Le Huy (Academia Journal of Biology, 2018)
The peanut worm, Siphonosoma australe australe (Keferstein, 1865), is a non-segmented worm, with a coelom, most live in areas of shallow water, tidal areas or the sea. Currently, the number of individuals in Peanut worm populations are declining considerably due to over-exploitation and habitat degradation. However, information on individual density and biomass of Peanut worm populations in Vietnam is still lacking, as is information on environmental factors affecting them. This study was carried out at various sites in the lower reaches of mangrove forest of the Gianh river, Quang Binh province. We calculated individual and hole densities per month by counting the number of individuals and holes according to each site area. We found significant differences (p ≤ 0.037) among sampled sites in hole density (from 1.43 to 2.54 holes/m2, average of 1,96 holes/m2), individual number (from 45 to 81 individuals, average of 62 individuals/site area), and biomass (from 20.27 to 51.16 g/m2, average of 34.57 g/m2). However, individual density (from 0.51 to 0.98 individuals/m2, average of 0.68 individuals/m2) was not significantly different among sites. Water temperature, pH, and salinity have the significant effect on individual and hole densities, individual number, and biomass of peanut worms (p ≤ 0.001; excepting water temperature affects the biomass of peanut worms). Excepting biomass, average individual and hole densities, as well as individual number of peanut worms, were greater in the dry season than in the rainy season (p < 0.0001).Keywords: Siphonosoma australe australe, biomass, density, mangrove forest, peanut worms, Gianh river.Citation: Nguyen Thi My Huong, Ngo Dac Chung, Le Huy Ba, 2018. Population density of the peanut worm Siphonosoma australe australe (Keferstein, 1865) (sipunculus:phascolosomatidae) in the mangrove forest of gianh river, Quang Binh province. Tạp chí Sinh học, 40(2): 138–144. https://doi.org/10.15625/0866-7160/v40n2.8511.*Corresponding author: myhuong_s4qt@quangbinh.edu.vn